Generation of N‐particle W State with Trapped Λ‐Type Ions by Transitionless Quantum Driving. Issue 3 (19th January 2021) - Liu, Yang; Shi, Zhi‐Cheng; Song, Jie; Xia, Yan
Abstract: An efficient scheme to generate multiparticle W state based on transitionless quantum driving (TQD) with trapped ions is proposed. In the TQD scheme, the effective Hamiltonian can be obtained with the help of quantum Zeno dynamics and large off‐resonance condition, and the multiparticle W state can be generated with high fidelity. The influence of decoherence induced by the ionic spontaneous emission and the ambient heating, and the sensitivity of the TQD scheme to some experimental errors are discussed by numerical simulation. The result demonstrates that the TQD scheme is faster than that only via the fractional stimulated Raman adiabatic passage and robust against decoherence and operation imperfection. Abstract : A universal scheme to generate N ‐particle W state with trapped Λ‐type ions with the help of transitionless quantum driving is given. The required counterdiabatic term is constructed by designing experimentally feasible control fields. Numerical simulations show the scheme is robust against different kinds of experimental imperfection and decoherent factors.